THE ROLE OF TEACHERS IN IMPROVING STUDENTS' WRITING SKILLS IN TK SURI TAULADAN KOTA PAGAR ALAM - Lestari, Lestari; Luzi, Ahmad Surya (Jurnal Konseling Pendidikan Islam, 2024)
Early childhood development is associated with psychological changes themselves, covering cognitive, linguistic, socio-emotional, religious, and moral aspects. Cognitive development in early childhood is concerned with all psychological processes related to knowledge, as well as the way the child learns and thinks about his environment. The purpose of this study is to determine the role of teachers in improving students' writing skills and to find out what obstacles teachers find in improving student's writing skills in Suri Tauladan Kindergarten in Pagar Alam City. The method in this study uses quantitative methods with the type of Classroom Action Research (PTK), which in English is called Classroom Action Research (CAR). The type of research used in this study is qualitative analysis research (assessment analysis), which uses data collection techniques using interviews, documentation, interviews, and observations. Students' writing skills have not developed. Therefore, one action is needed, namely the role of the teacher. The implementation of learning carried out by teachers can improve students' writing skills in Suri Tauladan Kindergarten in Pagar Alam City. In cycle I, students' writing skills are low, while in cycle II, it increases.